2020
DOI: 10.17576/jsm-2020-4912-15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shock Wave on Constant Load Behaviour of Pb-Free/Cnt Solder Joint

Abstract: The constant load behaviour of SAC305 solder joint with addition of carbon nanotube (CNT), exposed to shock wave condition was investigated. Formulated SAC305-CNT solder pastes with 0.04 wt. % CNT were manually printed to the printed circuit board (PCB) with copper surface finish to form solder joint. The solder joint was exposed to the shock wave condition via open field blast air test using Trinitrotoluene (TNT) explosive. Nanoindentation approach was used to determine the constant load behavior of the SAC30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Similarly, we discovered that the last pre-transfusional Hb level was an important associate of QoL. This was similar to the findings of an Indian study [ 13 ] and several foreign studies [ 15 , 20 , 21 ], which reported similar observations. It may be so because the optimal Hb level in the blood at any given point of time directly influences the physical and mental functioning and the overall QoL of a thalassemic child, just as it does for any other human being.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, we discovered that the last pre-transfusional Hb level was an important associate of QoL. This was similar to the findings of an Indian study [ 13 ] and several foreign studies [ 15 , 20 , 21 ], which reported similar observations. It may be so because the optimal Hb level in the blood at any given point of time directly influences the physical and mental functioning and the overall QoL of a thalassemic child, just as it does for any other human being.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the excellent mechanical properties of CNTs, they can bear most of the stress. Ismail et al [29] explained this mechanism through experimental results, showing that adding CNTs prevents sudden changes in the deformation mechanism in solder under shock waves. Compared with the SAC305 solder joints of the explosion test samples and the control samples, the indentation depth displacements of the SAC305-CNTs solder joints of the explosion test samples and the control samples were reduced by about 42% and 56%, respectively.…”
Section: Strengthening Mechanism Of Cnt Composite Soldermentioning
confidence: 99%
“…In addition, electronic devices are used in extreme environments, such as automotive, power electronics and aerospace engines, where solder joints are exposed to very high temperatures, often above of 200°C. Many previous works have reported the effects of harsh environments on the mechanical properties of solder joints in electronic devices (Lall et al , 2020; Sun et al , 2008; Ismail et al , 2020b). However, there are few studies that address the effects of radiation on the mechanical properties of solder joints in electronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of aging on the solder joint became more prominent as the aging time and temperature increased. Another study by Ismail et al (2020b) reported the constant load behaviour or creep properties of SAC305/CNT solder joints under shock wave conditions via the nanoindentation approach. As a result, exposure to shock waves degraded the creep properties of solder joints.…”
Section: Introductionmentioning
confidence: 99%